(untitled) (Ciencias Veterinarias, 2022)
A 5-year-old Costa Rican Paso stallion had a penis trauma during coitus and developed paraphimosis complicated with edema, hematoma, local infection, and cutaneous ulcerations. A literature review about relevant aspects of this topic is performed, including animal welfare in horse breeding. Considering that penis trauma is a relatively frequent problem in equines, it is important to publish this information to benefit the general veterinary practitioner working under field conditions without suitable equine hospital support, as it happens in some countries. This paper describes how to manufacture and use a homemade genital suspender (jockstrap) properly for the successful conservative management of the problem. General instructions to prevent accidents related to the equine coitus are mentioned; this is also an important topic to avoid animal abuse.